2016
DOI: 10.1080/07391102.2016.1243074
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the interaction procedure between Pt(IV) prodrug [Pt(5,5′-dmbpy)Cl4and human serum albumin: Combination of spectroscopic and molecular modeling technique

Abstract: In this study, a cytotoxic Pt(IV) complex [Pt(5,5'-dmbpy)Cl (5,5'-dmbpy is 5,5'-dimethyl-2,2'-bipyridine) was selected to investigate its affinity to human serum albumin (HSA) by spectroscopy and molecular docking methods. This complex has a bidentate nitrogen donor ligand with four chloride anions attached to a Pt(IV) metal in a distorted octahedral environment. The fluorescence data showed this complex quench the intrinsic fluorescence of HSA through a static quenching mechanism. The binding constant (K) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Crystal structure studies revealed that BSA possesses three homologues domains viz., domain I (1–195), domain II (196–383) and domain III (384–583) where each domain contains two subdomains (A and B). Subdomains IIA and IIIA are considered as the main binding sites, site I and site II respectively to which the small molecules bind [49]. The analysis of docked conformations clearly indicated that RPG was bound to BSA in the hydrophobic pocket of site II (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structure studies revealed that BSA possesses three homologues domains viz., domain I (1–195), domain II (196–383) and domain III (384–583) where each domain contains two subdomains (A and B). Subdomains IIA and IIIA are considered as the main binding sites, site I and site II respectively to which the small molecules bind [49]. The analysis of docked conformations clearly indicated that RPG was bound to BSA in the hydrophobic pocket of site II (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that three domains I–III (structurally similar) comprise the globular protein HSA. Each domain consists of two subdomains (A and B) [39–41]. Past observations have shown that most small molecules accumulate in areas where there are subdomains: IIA (site I) and IIIA (site II) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Each domain consists of two subdomains (A and B) [39][40][41]. Past observations have shown that most small molecules accumulate in areas where there are subdomains: IIA (site I) and IIIA (site II) [42].…”
Section: Quantum Mechanical Studies and Molecular Dockingmentioning
confidence: 99%
“…3D fluorescence spectroscopy is used to probe the conformational changes in structure of proteins [41–43]. We obtained the 3D spectra of HSA and HSA–La NPs system (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activity of HSA will be changed due to the structure variation of it [40]; therefore La NPs can change the biological activity of HSA significantly. 3.9 3D fluorescence spectroscopy 3D fluorescence spectroscopy is used to probe the conformational changes in structure of proteins [41][42][43]. We obtained the 3D spectra of HSA and HSA-La NPs system (Fig.…”
Section: Discussionmentioning
confidence: 99%